Design & Simulation of Microstrip Trapezoidal Patch Antenna with H and V Shaped slot (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper consists of two small Microstrip patch antenna. with H shaped and V shape slot. A trapezoidal patch is designed on a RT duroid substrate with relative permittivity of 2.2 and height of 6mm. A series of parametric study were carried out to show the dependence of the characteristics of the antenna on its various geometrical parameters Microstrip antenna is widely used in practical applications like wi-fi, wlan etc An Soft HFSS Vs 12 software which is based on finite element method , showed satisfactory performance with VSWR<2 for resonating frequencies